Comparative Analysis of Factors Affecting the Prognosis of Patients with Atrial Fibrillation According to the Results of the REKUR-AF Study - I. L. Polshakova; S. V. Povetkin (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To conduct a comparative analysis of the significance of the influence of various factors and their combinations on the survival of patients with atrial fibrillation (AF) in the REKUR-AF study.Material and methods. The database includes 896 patients with AF over 18 years old who applied to medical organizations in the city of Kursk and seven districts of the Kursk region from September 2015 to August 2016. Achievement by the patients of the “end point” (death from any cause) was assessed using a telephone contact for a period of 9.0±0.55 months from the end of the database formation. Data were obtained on 532 patients, of which 60 patients reached the end point. To study the differences in survival in subgroups of patients with different characteristics, two groups of categorized factors were analyzed – clinical (sex, age, form of AF, etc.) and pharmacological (use of different classes of drugs). The necessary information was obtained from outpatient cards analyzed when patients were included in the study.Results. The survival rate of patients with AF was significantly (p<0.05-0.001) influenced by the following factors and their categories: age (<60 years – 92.5%, 60-65 years – 92.9%, over 75 years – 80.1%); AF form (paroxysmal – 95.1%, persistent – 93.2%, permanent – 84.4%); stable angina (SA) (presence – 86.5%, absence – 90.7%); chronic heart failure functional class (CHF FC) (I-II – 95.9%, III – 91.5%, IV – 69.6%); glomerular filtration rate (GFR) (>50 ml/min – 89.6%, 30-50 ml/min – 85.8%, <30 ml/min – 72.7%); diabetes mellitus (DM) (presence – 81.9%, absence – 90.4%), hospitalization for the year preceding inclusion in the study (presence – 85.5%, absence – 97.3%), the use of oral anticoagulants (OAC) (presence – 96.7%, absence – 87.1%). In subgroups of patients with the above mentioned categories (especially the most severe) of the studied factors, significant (p<0.05-0.01) differences in the proportion of surviving patients depending on the appointment of OAC were revealed: age >75 years – 78.2% and 100%; permanent form of AF – 81.9% and 96.1%, the presence of SA – 85.0% and 94.7%; CHF FC IV – 67.0% and 91.7%; GFR<30 ml/min – 62.5% and 100%; presence of DM – 80.7% and 88.2%.%; the presence of hospitalizations in the last year – 82.9% and 97.2%; >5 points on the CHA2DS2VASc scale – 67.0% and 91.7%, heart rate >90/min – 68.8% and 100% of patients with the absence and presence of the OAC therapy, respectively. Cox regression analy sis revealed clinical predictors contributing to an increase in the risk of death: age over 75 years, permanent form of AF, CHF FC III-IV, the presence of DM, the presence of previous hospitalizations. The absence of the OAC taking was accompanied by an increase in the risk of death by 3.66 times.Conclusion. The results of the REKUR-AF study allowed to establish the most significant factors affecting the survival of patients with AF: age, form of AF, CHF FC, presence of DM, hospitalization in the last year preceding the inclusion of patients in the study, OAK taking. The prescription of OAC is a priority predictor that improves survival in patients with AF.